The Fatal Accident at Biodiversity Flyover in Hyderabad - A Case Study - Raja Sekhar Mamillapalli,; Srihari Vedartham, (International Journal of Engineering and Management Research, 2021)
Urban disasters, Traffic is unavoidable due to increase in density of vehicles without adding more road space to the city. This is demanding for more flyovers, grade separators to avoid congestion at the junctions. Hyderabad is congesting with many junctions adding up to the heavy traffic and waiting time, energy, fuel and polluting the city with noise and air pollution. For economic benefit and decongestion of major junctions, Flyovers were planned and constructed. To meet this demand in Gachibowli and Hi-Tech city area, a flyover was constructed by MVR Infra projects near biodiversity junction. The present paper describes the incident of fatal accident taken place on November 23, 2019. The study also reveals aftermath actions taken by the government of Telangana and suggested various sections in the Indian penal codes for such incidents.